Sideways Arithmetic from Wayside School - Sachar, Louis (New York, NY : Scholastic, 1989)
Everyone take out your spelling books," said Mrs. Jewls. "It's time for arithmetic." Sue is so excited for her first day at Wayside School. But things at Wayside are far from normal-and Sue's teacher, Mrs. Jewls, is completely wacky. She expects the students to add and subtract words! Sue has never heard of anything so ridiculous. She knows adding apples plus oranges is impossible ... or is it? Anything can happen at Wayside School.
"An Apple paperback."
670L
Keywords: Mathematical recreations -- Juvenile literature; Puzzles -- Juvenile literature; Arithmetic -- Problems, exercises, etc -- Juvenile literature